Functionally important structural elements of U12 snRNA - Sikand, Kavleen (Oxford University Press, 2011)
U12 snRNA is analogous to U2 snRNA of the U2-dependent spliceosome and is essential for the splicing of U12-dependent introns in metazoan cells. The essential region of U12 snRNA, which base pairs to the branch site of minor class introns is well characterized. However, other regions which are outside of the branch site base pairing region are not yet characterized and the requirement of these structures in U12-dependent splicing is not clear. U12 snRNA is predicted to form an intricate secondary structure containing several stem–loops and single-stranded regions. Using a previously characterized branch site genetic suppression assay, we generated second-site mutations in the suppressor U12 snRNA to investigate the in vivo requirement of structural elements in U12-dependent splicing. Our results show that stem–loop IIa is essential and required for in vivo splicing. Interestingly, an evolutionarily conserved stem–loop IIb is dispensable for splicing. We also show that stem–loop III, which binds to a p65 RNA binding protein of the U11-U12 di.snRNP complex, is essential for in vivo splicing. The data validate the existence of proposed stem–loops of U12 snRNA and provide experimental support for individual secondary structures.